EXPLORING TEACHERS’ PERCEPTIONS OF FORMATIVE ASSESSMENT PRACTICES IN ENGLISH LANGUAGE CLASSROOMS - Fitri Ade Andriani; Ira maisarah (English Study Program University of Pasir Pengaraian, 2026)
Formative assessment has been recognised as a crucial strategy in enhancing teaching and learning in English as a Foreign Language (EFL) classrooms. Few studies have specifically investigated teachers' perceptions of different types of formative assessment techniques in an EFL setting in secondary schools in Bengkulu, Indonesia. This study was designed to explore teachers' perceptions of formative assessment practices.This study used descriptive quantitative survey design with 34 active English teachers as samples selected using purposive sampling technique. The researcher used a 40 item questionnaire to gather data, adapted from the research conducted by Kausar (2023) on eleven formative assessment techniques. The data were also analyzed using descriptive statistics such as means, standard deviations, and percentages, to find the level of teachers' perception.The findings showed that teachers' attitudes towards formative assessment practices were mostly positive. Techniques such as questioning, classroom discussion, feedback, encouraging positive behaviour, personal experience activities, portfolios, one-minute papers, and appraising good values were perceived as effective in promoting student engagement and learning. However, several techniques, including multiple-choice questions, think-pair-share activities, and storytelling, received moderate responses due to challenges related to student pressure, memorization, participation, and attention management during classroom implementation.This study provides contextual information on formative assessment in EFL classrooms in Indonesia, specifically in Bengkulu province, where there are few empirical studies. The results indicate the necessity of designing and implementing targeted professional development strategies to enhance teachers' ability and capacity for the effective and sustained implementation of formative assessment techniques to aid student learning and academic performance.